Hubungan Perilaku Masyarakat dan Peran Kader dengan Kejadian Demam Berdarah Dengue: The Relationship Between Community Behavior and the Role of Health Cadres with the Incidence of Dengue Hemorrhagic Fever - Faiza Candrarini Widyadana; Teti Oktianingsih; Dayuningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia and is closely associated with community preventive behavior and the role of health cadres in vector control. Objective: This study aimed to analyze the relationship between community behavior and the role of health cadres with the incidence of Dengue Hemorrhagic Fever in the working area of Jalan Emas Public Health Center, Tangerang Regency. Methods: This study employed an analytical observational design with a cross-sectional approach. The population consisted of households in the working area of Jalan Emas Public Health Center. A total of 81 respondents were selected using simple random sampling. Data were collected using structured questionnaires and analyzed using Fisher’s Exact Test. Results: The results showed that most respondents had moderate dengue prevention behavior (63.0%), and more than half perceived the role of health cadres as good (58.0%). Statistical analysis revealed a significant relationship between community preventive behavior and dengue incidence (p < 0.05). A significant relationship was also found between the role of health cadres and dengue incidence (p < 0.05). Respondents with good preventive behavior and positive perceptions of cadre roles were less likely to experience dengue infection. Conclusion: Community preventive behavior and the role of health cadres are significantly associated with the incidence of Dengue Hemorrhagic Fever.